Combined Neuroleptic Analgesia in Acute Coronary Heart Disease - O.V. Voennov; G.A. Boyarinov (Общая реаниматология, 2006)
The aim of investigation was opthimizaition an analgesia in patients with the acute forms of an ischemic heart, based on a combination of phentanyl, tramadol and droperidol. It proceeds from a comparative analysis of the investigating vales that a use of the phentanile-tramadole neuroleptanalgesia permits to more adequately conduct an analgesia, normalized the hemodynamics values, has better prognosis. Key words: acute forms of an ischemic heart disease, anginal pains, neurolep-tanalgesia, phentanyl, tramadol, droperidol.